Partners in Learning: An Investigation into a Service-Learning Module for Community Partners and Occupational Therapy Students - KENNEDY, ISABEL MAY (Trinity College Dublin. School of Medicine. Discipline of Occupational Therapy, 2018)
Service-learning is a pedagogical approach to learning which aims to link academic coursework to real word situations through the provision of service (Eyler & Giles, 1999). The body of literature concerning service-learning has focused predominantly on student outcomes (Warren, 2012; Yorio & Ye, 2012). There are comparatively few studies concerning community organisations as partners and almost none examining individual community partner. Relationship building, and mutual benefit are fundamental concepts underpinning service-leaning theory (Dewey, 1916; Bringle et al., 2009) and while some studies have begun to examine partnerships between universities and organisations (Blouin & Perry, 2009; Tinkler et al., 2014), there is a dearth of research into the relationships between students and individual community partners. Research Aims: This study aimed to address this gap in the literature by examining the outcomes and perceptions of community partners and first and second-year occupational therapy students in a service-learning module. Five areas were examined: (i) to explore the understanding and the nature of the service-learning relationship (ii) to examine the impact of service-learning on community partners’ and students’ personal and professional development (iii) to understand the effect of service-learning on occupational engagement and participation (iv) to measure changes to students’ attitudes towards disability as a result of service-learning and (v) to explore students’ growth and learning through the use of guided reflection. Methodology: This convergent parallel mixed methods study over two phases used a pre- and post- survey design in the quantitative aspects to examine the relationship between students and their partners, attitudes towards disability, personal and professional skills and occupational competence and values. In addition, qualitative data was collected through the use of focus groups and student reflective workbooks. Results: The results from all strands of data were triangulated and integrated to create three main themes of outcomes: ‘the nature of the service-learning relationship’, ‘service-learning partners as occupational beings and their engagement and participation’ and ‘outcomes of service-learning relationship’. This study found that students and community partners gained a greater understanding of the service-learning relationship over the course of the service-learning module. Through developing positive, reciprocal relationships, students and community partners created a supportive social environment in which occupational participation and engagement was fostered. Community partners’ and students’ value of everyday occupations increased by the end of the module. In addition, students’ occupational competence increased. Community partners’ perceived value of daily occupations also increased. Students’ attitudes towards disability improved. It is suggested the relationships experienced in this service-learning module may have been transformational.
APPROVED
Keywords: service-learning; occupational therapy; community partners; transformational relationships; attitudes; learning; personal development; professional development; occupational spin-off; co-occupation; students; occupational engagement; social inclusion; social justice; reflection